Treatment of refractory lupus nephritis using leflunomide: A prospective study - Zhang, Shuo; Chen, Yiran; Chen, Xin; Zhao, Yan; Zeng, Xiaofeng; Zhang, Fengchun; Wang, Li; Li, Mengtao (Frontiers in Immunology, 2023)
Introduction: Refractory lupus nephritis (LN) is a common complication that negatively affects the life expectancy and disease prognosis of patients with systemic lupus erythematosus, posing a challenge in their clinical management. This interventional study evaluated the efficacy and safety of leflunomide in patients with refractory LN. Methods: Twenty patients with refractory LN were enrolled in this study. The patients received leflunomide orally at a dose of 20–40 mg per day. The dose of corticosteroids was gradually tapered and immunosuppressants were withdrawn. Most patients were followed-up after 3, 6, and 12 months, while some were observed for a period of up to 24 months. Biochemical parameters and side effects were recorded. Intention-to-treat analysis was performed to calculate the response rate. Results: Eighteen participants (90 %) completed the study. At 3 months, 80 % (16/20) of the patients achieved more than a 25 % decrease in 24-hour urine protein quantity. At 6 months, three patients (15 %) achieved a partial response, and five patients (25 %) achieved a complete response. However, the complete response rate decreased to 15 % at 12 months and 20 % at 24 months. The objective responses were 30 % (6/20), 40 % (8/20), 40 % (8/20), and 30 % (6/20) at 3, 6, 12, and 24 months, respectively. Two patients withdrew from the study due to developing cytopenia and leucopenia. Conclusion: This study shows that leflunomide could be a promising treatment option for patients with refractory LN owing to its response rate and safety profile.